Health Promotion Dengan Video Untuk Meningkatkan Kedisiplinan Memakai Masker Siswa Sekolah Dasar Pelita Bangsa Dalam Kehidupan Pada Masa New Normal - Vitaria Wahyu Astuti; Kili Astarani; Fidiana Kurniawati (Pelita Medika, 2022)
Background: New Normal is a change in habits in carrying out daily activities during the COVID-19 pandemic, it requires high discipline in implementing health protocols, one of which is wearing masks correctly. Children are a vulnerable group in disasters because children need special assistance in making decisions in every action taken. Method: Conducting Health Promotion by using Video as an effort to increase children's discipline in the use of masks to reduce the number of diseases caused by the coronavirus. Results: Based on direct observations in the field, there was a significant increase in the use of proper masks for Pelita Bangsa Elementary School students Conclusion: Health Promotion with Video can improve the discipline of Pelita Bangsa Elementary School students in using masks correctly